Pendampingan Pembuatan Mini Gardening dalam Upaya Meningkatkan Kreativitas Siswa - Dyah Ayu Sri Hartanti; Wisnu Siwi Satiti; Ulfa Wulan Agustina; Suci Prihatiningtyas; Ino Angga Putra; Devva Amrita Pramusari; Lailatul Hidayah; Mohamad Ahya Assyukri (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
The issue of low environmental awareness among elementary school students often manifests in their indifference toward school gardens and waste management, which reflects limited ecological literacy and weak practical skills in sustainable living. This community service program focused on implementing a Mini Gardening Class designed to foster creativity, responsibility, and environmental care among sixth grade students at an Islamic elementary school. The objective was to integrate gardening activities as both an educational tool and a life skills training program that nurtures environmental awareness and simple entrepreneurship in agriculture. The method applied was service learning, combining direct practice, participatory learning, and reflection to strengthen character and knowledge. Students were guided through activities such as preparing organic media from banana stems, husks, and compost, creating liquid fertilizer from rice water, planting short-harvest vegetables, and maintaining their growth through daily care. The strategy emphasized experiential learning, collaborative teamwork, and integration with science and character education subjects. The results showed a significant increase in students’ knowledge and skills in gardening, higher enthusiasm for outdoor learning, and improved responsibility in maintaining the school garden. Furthermore, the program produced practical outputs including a gardening manual, sustainable planting media, and organic fertilizer that could be replicated by the wider community. This activity successfully transformed idle school land into a productive and educational space, while also instilling values of sustainability, cooperation, and independence. It is expected that the Mini Gardening Class can serve as a sustainable model of environmental education and food self-sufficiency in schools.